The education of Dixie Dupree [large type] - Everhart, Donna (Center Point Large Print, 2016)
"In 1969 Alabama, eleven-year-old Dixie Dupree learns that the family she once believed was happy has deep fractures and records everything in her diary in this coming-of-age story about mothers and daughters, the guilt and pain that pass between generations, and the truths that are impossible to hide, especially from ourselves"--